Analisis and improvement of the warehouse of finished products in Rum Factory - González Cabrera, Ernesto; Glistau, Elke; Cespón Castro, Roberto; Coello Machado, Norge Isaías (My University, 2020)
The development of the global economy and consumer demands make the manufacture and production of items more reliable and transparent every day, in the case of food, it is essential in today's market to ensure the safety of food and beverages. One of the fundamental tools to guarantee this process is the certification of the areas destined to store the products, for their distribution or reception by the clients. In the present research, an extensive review of the literature is carried out; where performance indicators used by different companies responsible for certifying the structures of the warehouses or the storage system used are evaluated. The best practices used for its improvement and better performance in the entities and the safety and hygiene required by the product are taken into account. As an application, a case study is presented with a view to the certification of the building for the storage of the finished production of its logistics system in the Ron Cubay production process.
Keywords: Certification; Warehouses; Performance Indicators; Supply Chain; Logística Empresarial